Anisotropic ionic conductivity of LiMn1−xFexPO4 (0 ≤ x ≤ 1) single crystals - Neef, Christoph; Reiser, Andreas; Thauer, Elisa; Klingeler, Rüdiger (Solid state ionics, 2020)
We report AC-impedance studies on a series of high-quality LiMn1−xFexPO4 single crystals with 0 ≤ x ≤ 1. Our results confirm quasi-one-dimensional transport in LiFePO4 with fast Li-diffusion along the b-axis. The conductivities along the crystallographic b-, c- and a-axis differ by a factor of about 10, respectively. Whereas, the activation energy EA of the effective diffusion process is particularly large for the b-axis and smallest for the a-axis. Remarkably, the b-axis ionic bulk conductivity of LiMn0.5Fe0.5PO4 is of the same order of magnitude as in undoped LiFePO4, which implies similarly fast Li-transport even upon 50% Mn-doping which, owing to the higher redox potential of the Mn3+/Mn2+-couple, yields enhanced energy density in lithium-ion batteries. The overall results of our impedance studies draw a far more complex picture than it would be expected from a simple one-dimensional ionic conductor. Our results suggest a strong contribution of crystal defects in actual materials.